2022
DOI: 10.1155/2022/1384609
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Concentrations of NSE, S100β, Aβ, and Proinflammatory Cytokines in Elderly Patients Receiving Ultrasound-Guided Combined Lumbar Plexus-Sciatic Nerve Block during Hip Replacement

Abstract: Objective. The increase of hip fractures is related to the aging of the population, which has caused a huge medical burden in many countries. Hip replacement has been approved as a highly successful surgical intervention for the patients with hip fractures. Different anesthesia choices in the surgical intervention are associated with the prognosis of patients. This study focused on investigating the application of ultrasound-guided combined lumbar plexus-sciatic nerve block in elderly patients with hip fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Wang et al [ 17 ] applied BCFS to treat femoral fractures, and no postoperative implant fracture, wound infection, or other serious complications occurred, similar to our research results. Finally, we detected three serum proinflammatory markers, namely, TNF- α , IL-1 β , and IL-6; the three are highly correlated with patients' immune response, and their increased concentrations will reduce patients' immune function [ 22 ]. The results showed that postoperatively, the three indexes in OG were significantly lower than those before treatment and CG, which suggested that BCFS had an inhibitory effect on the inflammatory response of patients with periarticular fractures of the shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 17 ] applied BCFS to treat femoral fractures, and no postoperative implant fracture, wound infection, or other serious complications occurred, similar to our research results. Finally, we detected three serum proinflammatory markers, namely, TNF- α , IL-1 β , and IL-6; the three are highly correlated with patients' immune response, and their increased concentrations will reduce patients' immune function [ 22 ]. The results showed that postoperatively, the three indexes in OG were significantly lower than those before treatment and CG, which suggested that BCFS had an inhibitory effect on the inflammatory response of patients with periarticular fractures of the shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…Using ultrasound equipment during nerve block, anesthesia may have contributed to this outcome by allowing for accurate localization and minimizing the risk of nerve damage, thereby promoting the reduction of postoperative pain; this may also mitigate the likelihood of chronic pain development [ 24 ]. Effective postoperative pain management improves patient recovery and reduces persistent pain [ 15 , 18 , 25 ]. Conversely, the GEA group’s use of the short-acting opioid Remifentanil may have contributed to the observed nociceptive hypersensitivity, potentially exacerbating postoperative pain [ 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…PNB with ultrasound guidance have garnered increased acceptance stemming from their heightened efficacy and capacity to ameliorate systemic complications associated with GEA. In contrast to the adverse impact of the latter on cardiopulmonary function, ultrasound-guided PNB have proved instrumental in not only impeding the activation of inflammatory factors [ 14 , 15 ] but also in restraining the physiological reaction engendered by surgical trauma, thereby curtailing the accompanying injury. In this retrospective study, we examined the impact of GEA and PNB anesthetic techniques on intraoperative hemodynamics, postoperative analgesia, and treatment results for DFUs.…”
Section: Introductionmentioning
confidence: 99%
“…Regional anesthesia techniques offer benefits compared to general or spinal anesthesia. Peripheral nerve blocks (PNBs) have emerged as innovative alternatives, exhibiting benefits in hemodynamic stability, reduced complications, and shorter hospital stays [30] [48]. In the elderly, where hip fractures often present significant risks, research also demonstrates the success of peripheral nerve blocks, even in highrisk patients.…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%
“…Nerve blocks, by minimizing complications have the potential to reduce healthcare costs associated with prolonged hospital stays. Utilizing peripheral regional anesthesia in hip surgeries is linked to enhanced hemodynamic stability and a decreased incidence of complications, presenting a favorable alternative to general or spinal anesthesia [30]. Within this patient population, localized anesthesia, specifically peripheral and neuraxial nerve blocks, is associated with a reduced risk of pulmonary complications, postoperative cognitive dysfunction, and shorter intensive care unit stays [31].…”
Section: Reduced Complicationsmentioning
confidence: 99%